2017
DOI: 10.1016/j.im.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Technology-induced anxiety: Manifestations, cultural influences, and its effect on the adoption of sensor-based technology in German and Australian hospitals

Abstract: Sensor-based systems have healthcare transformation potential but acceptance problems jeopardize their diffusion. We theorize that perceived technology threats induce anxiety and diminish usage intentions. We use data from the pre-implementation phase in German and Australian hospitals to explore the formation of three types of anxieties, their impact on usage intentions, and the relationships between them and national culture. We find negative effects of relational and work-related anxieties on usage intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 134 publications
(169 reference statements)
5
40
0
1
Order By: Relevance
“…Moreover, studies have mentioned the importance of domain of organizational readiness, which reflects the overall preparedness for health technology and preference tendency of the entire staff, it consists of three factors: organizational culture, technology absorptive willingness and technology sharing willingness. Organizational culture is the ensemble of values, norms, beliefs, language patterns and operating behaviors shared by individuals or groups within an organization, such as RMC or a hospital within it [27,28]. Technology absorptive willingness show the willingness and readiness situations of introducing a new health technology into the organization [29], while technology sharing willingness is a degree of sharing knowledge with the other organizations [30,31].…”
Section: {Insert Figure 1 Here}mentioning
confidence: 99%
“…Moreover, studies have mentioned the importance of domain of organizational readiness, which reflects the overall preparedness for health technology and preference tendency of the entire staff, it consists of three factors: organizational culture, technology absorptive willingness and technology sharing willingness. Organizational culture is the ensemble of values, norms, beliefs, language patterns and operating behaviors shared by individuals or groups within an organization, such as RMC or a hospital within it [27,28]. Technology absorptive willingness show the willingness and readiness situations of introducing a new health technology into the organization [29], while technology sharing willingness is a degree of sharing knowledge with the other organizations [30,31].…”
Section: {Insert Figure 1 Here}mentioning
confidence: 99%
“…For this paper, organizational readiness consists of three factors: organizational culture, technology absorptive willingness and technology sharing willingness. Organizational culture is the ensemble of values, norms, beliefs, language patterns and operating behaviors shared by individuals or groups within an organization, such as RMC or a hospital within it [37,38]. Technology absorptive willingness shows the willingness and readiness situations of introducing a new health technology into the organization [39], while technology sharing willingness is a degree of sharing knowledge with the other organizations [40,41].…”
Section: Domains and Dimensionsmentioning
confidence: 99%
“…Research has shown that stress and anxiety related to technology can have negative effects on individual and organisational outcomes: For example, technostress results in perceived work overload, demoralized and frustrated users, information fatigue, loss of motivation, dissatisfaction at work, decreased organisational and continuance commitment, decreased individual productivity and increased role stress (Brod 1984;Ragu-Nathan et al 2008;Tarafdar et al 2007). Technology anxiety negatively influences role clarity, motivation, and perceived ability (Meuter et al 2005) and can significantly influence the acceptance of newly introduced systems (Kummer et al 2017).…”
Section: Introductionmentioning
confidence: 99%